Oesophageal stricture in a cat with true pleuroperitoneal hernia - Yeon Chae; Taesik Yun; Yoonhoi Koo; Dohee Lee; Yelim Lee; Dongwoo Chang; Mhan‐Pyo Yang; Byeong‐Teck Kang; Hakhyun Kim (Veterinary Medicine and Science, 2024)
Abstract A 2‐year‐old neutered male Bengal cat presented with solid food dysphagia and chronic regurgitation for >5 months. There were no clinical abnormalities on haematological or radiographic examinations. Thoracic radiography revealed a soft tissue opacity mass adjacent to the diaphragm in the caudoventral thorax. Ultrasonography revealed a protruding liver lobe surrounded by a hyperechoic lining from the diaphragm towards the thorax, and a pleuroperitoneal hernia was diagnosed. An endoscopy was performed to examine the cause of regurgitation, and an oesophageal stricture was observed. Endoscopic balloon dilation of the oesophageal stricture was performed, and the regurgitation was resolved immediately. However, regurgitation relapsed 2 months later, and computed tomography was performed to ascertain the cause. Computed tomography revealed oesophageal mural thickening and true pleuroperitoneal hernia with partial liver lobe herniation. A second endoscopy with balloon dilation was performed to treat the relapsing oesophageal stricture, and the clinical signs resolved without the need for herniorrhaphy. Nevertheless, oesophageal stricture could occur due to gastroesophageal reflux related to a pleuroperitoneal hernia; however, a definite link could not be elucidated in this case. This report describes a case of oesophageal stricture and concurrent true pleuroperitoneal hernia in a cat.